Model of Teachers’ Potential in Learning Management to Enhance of Student’s Thinking Skill Based on Local Wisdom - Meesup, Phutcharawalai (Ratchaphruek Journal, 2022)
The purposes of this research were to study 1) the needs and problems of learning management (LM) to enhance of student’s thinking skill, 2) the effectiveness of LM model to enhance of student’s thinking skill based on local wisdom, 3) the results of using LM model, and 4) satisfaction in LM model based on local wisdom. The samples in the study of needs were 318 teachers, validation model effectiveness by 5 experts, and the samples in using LM model were 15 teachers and 23 students The research instruments were questionnaire, knowledge test, LM ability form and thinking skills test. The data were analyzed using PNI modified, mean, standard deviation and Wilcoxon signed-rank test. The findings were as follows: 1) The results found that the most important aspects were LM, 2) The models of model of teachers’ potential had 5 elements: principles, objectives, content, the process of activities, and evaluation, 3) The teachers had a statistically significantly higher level of comprehension after training more than before training at .05 level, the quality of competence in LM was at a high level, and student had a statistically significantly higher level at .05 level, and 4) The satisfaction with the model of teachers’ potential in LM to enhance of student’s thinking skill based on local wisdom was at a high level.